Cardiopulmonary exercise test and heart failure biomarkers results after comprehensive rehabilitation of LVAD patients. (3rd October 2022) - Chwyczko, T; Smolis-Bak, E; Zalucka, L; Segiet-Swiecicka, A; Piotrowicz, E; Was, J; Niedolistek, M; Kowalik, I; Sobieszczanska-Malek, M; Zielinski, T; Szymanski, J; Kusmierczyk, M; et al.
Abstract: Background: The novel method of comprehensive rehabilitation after left ventricular assist device (LVAD) implantation was developed in our institution. Cardiopulmonary exercise test was used to program the training and to assess the results of rehabilitation. Study group: 47 consecutive LVAD (32 Heart Mate III, 15 HeartWare) recipients (19–68 years, mean 58.7 years, 43 men) participated in the rehabilitation program. Proposed 4–5 week program included supervised endurance training on cycloergometer (5 times per week), resistance training, general fitness exercises with elements of equivalent and coordination exercises (every day). It was followed by individual exercises performed at home. 6-minute walk test (6MWT), cardiopulmonary exercise test (CPET) and prognostic biomarkers of heart failure: NT-proBNP, Galectin-3 and ST2 were investigated at the beginning and at the end of rehabilitation program. Results: See Table 1. Increase of 6MWT distance, higher maximal workload, peak VO2 and upward shift of anaerobic threshold (AT) in CPET were observed in all patients. Significant reductions of NTproBNP, ST2 and galectin-3 levels were observed. There were no major adverse events during rehabilitation. Conclusions: Comprehensive novel rehabilitation in LVAD recipients is safe and results in significant improvement of functional tests and biomarkers of heart failure. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Centre for Research and Development